2007
DOI: 10.2214/ajr.05.1067
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Sonography for Nasal Fracture in Children

Abstract: Sonography can be a primary diagnostic technique for evaluating nasal fracture in children. It inflicts no radiation, provides various imaging planes without positional change, and can be used to evaluate the cartilaginous septum. Potential pitfalls are the nasofrontal suture, the junction between the nasal bone and the pyriform aperture of the maxilla, the vascular groove, and the presence of an old fracture. CT can be used in addition to sonography in cases of suspected complex facial bone trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 12 publications
3
68
0
Order By: Relevance
“…All participants underwent nasal ultrasongraphy using a small linear 7.5 MHz transducer (Aloka 3500, Tokyo, Japan) which was placed parallel to the nasal bone without a stand-off pad 3 by a radiologist who has 10 years clinical experience and is an expert in soft-tissue and musculoskeletal imaging. The radiologist was blind to the CT findings.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All participants underwent nasal ultrasongraphy using a small linear 7.5 MHz transducer (Aloka 3500, Tokyo, Japan) which was placed parallel to the nasal bone without a stand-off pad 3 by a radiologist who has 10 years clinical experience and is an expert in soft-tissue and musculoskeletal imaging. The radiologist was blind to the CT findings.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging procedures in midface traumas are also needed for forensic reasons. 3 Although a routine radiographic examination is the main diagnostic tool for traumas to the nose, it is not very accurate and it is difficult to determine which side is fractured on conventional radiographs. 4,5 CT has been considered as a gold standard and it is the procedure of choice for diagnosing complex facial fractures, especially mid-facial fractures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many fracture types, such as zygomatic arch (4), calcaneal fracture (5) (6) can be accurately imaged with bedside US. Hong HS et al (7). concluded that sonography can be a primary diagnostic technique for evaluating nasal fractures in children.…”
Section: Discussionmentioning
confidence: 99%